The Effect of Training, Mentoring, and Resilience on Employee Performance is Mediated by Employee Engagement - Ahmad Faisal (Dinasti Publisher, 2024)
The article The Effect of Training, Mentoring and Resilience on Employee Performance Mediated by Employee Engagement is a scientific literature article within the scope of human resource management science. The purpose of this writing is to build a hypothesis of the influence between variables which can later be used for further research within the scope of human resource management. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and Sinta journals. The results of this article are: 1) Training influences employee engagement; 2) Mentoring influences employee engagement; 3) Resilience influences employee engagement; 4) Training influences employee performance; 5) Mentoring influences employee performance; 6) Resilience influences employee performance; 7) Employee engagement influences employee performance; 8) Training influences employee performance through employee engagement; 9) Mentoring influences employee performance through employee engagement; and 10) Resilience influences employee performance through employee engagement.